Pengaruh Ekstrak Daun Kenikir (Cosmos caudatus Kunth.) pada Histopatologi Hepar Tikus Putih (Rattus norvegicus L.) Induksi Aspirin - Ayunda, Sapna; Febriani, Husnarika; Syukriah, Syukriah (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Aspirin is one of the most commonly used nonsteroidal anti-inflammatory drugs (NSAIDs); however, long-term use and high doses can damage liver function and structure. To reduce aspirin’s side effects, kenikir leaves (Cosmos caudatus K.) are used as an alternative treatment. This study aims to evaluate the effects of kenikir leaf extract on liver damage caused by aspirin, both morphologically and histopathologically. A total of 25 male white rats were divided into 5 groups: KN (control), KP (aspirin 200 mg/kg BW for 10 days), P1 (aspirin + kenikir extract 700 mg/kg BW for 14 days), P2 (aspirin + kenikir extract 800 mg/kg BW for 14 days), and P3 (aspirin + kenikir extract 900 mg/kg BW for 14 days). Liver cell damage was analyzed using scoring and histomorphometry methods, followed by one-way ANOVA and Duncan’s test. The results showed that kenikir leaf extract significantly improved the morphology and histopathology of rat livers induced by aspirin, including parenchymal degeneration, hydropic degeneration, and necrosis. The most effective dose was 800 mg/kg BW, which also improved the diameter of the central vein and the width of the liver sinusoids.